Identity of Virtual Supporters: Constructing Identity of Turkish Football Fans on Digital Media - Atici, Bunyamin; Bati, Ugur (Igi Global, 2013)
The main purpose of this study is to develop a framework Jar understanding and analyzing digital media as an autonomous social space or structure in which to construct an identity This chapter extends debate on the impact of developing an online identity by focusing on football supporters, a specific and prevalent community within Turkish society. The authors examine issues surrounding online identity and the impact of digital culture on football supporters through questionnaires conducted with members of fan-based web sites, football forums, and football blogs in Turkey In the research, the authors focus on the digital identity of fans from the three major clubs of Turkey - Besiktas, Fenerbahce, and Galatasaray. The independent football fan communities of Carsi, UltrAslan, and Gencfb are also present in the digital environment in the form of the official Websites of these fan communities at www.forzabesiktas.com, www.ultraslan.com, and www.gencfb.org. The three main websites also include different forums and blogs. This research examines the impact of digital media and distributed social spaces of these clubs' supporters on contemporary understandings of their digital identity The authors give the conceptual frameworks and approaches to understanding digital identity of football fans. In this context, authenticity fanaticism, reputation, belonging, and defending identity are examined to understand individual, group, community, and network based digital identities. From a theoretical perspective, the chapter also tries to understand what it means to he a part of a community using digital media.